Epidermal clearance of Candida albicans is mediated by IL-17 but independent of fungal innate immune receptors. (31st May 2022) - Iwasawa, Mari T; Miyachi, Hideaki; Wakabayashi, Seiichiro; Sugihira, Takashi; Aoyama, Reika; Nakagawa, Seitaro; Katayama, Yuki; Yoneyama, Mitsutoshi; Hara, Hiromitsu; Iwakura, Yoichiro; Matsumoto, Masanori; Inohara, Naohiro; et al.
Abstract: Abstract IL-17 plays important roles in host defense against Candida albicans at barrier surfaces and during invasive infection. However, the role of IL-17 in host defense after colonization of the epidermis, a main site of C. albicans infection, remains poorly understood. Using a murine model of epicutaneous candidiasis without skin abrasion, we found that skin inflammation triggered by epidermal C. albicans colonization was self-limiting with fungal clearance completed by day 7 after inoculation in wild-type mice or animals deficient in IL-17A or IL-17F. In contrast, marked neutrophilic inflammation in the epidermis and impaired fungal clearance were observed in mice lacking both IL-17A and IL-17F. Clearance of C. albicans was independent of Dectin-1, Dectin-2, CARD9 (caspase-recruitment domain family, member 9), TLR2 (Toll-like receptor 2) and MyD88 in the epidermal colonization model. We found that group 3 innate lymphoid cells (ILC3s) and γδT cells were the major IL-17 producers in the epicutaneous candidiasis model. Analyses of Rag2 −/− mice and Rag2 −/− Il2rg −/− mice revealed that production of IL-17A and IL-17F by ILC3s was sufficient for C. albicans clearance. Finally, we found that depletion of neutrophils impaired C. albicans clearance in the epidermal colonization model. Taken together, these findings indicate a critical and redundant function of IL-17A and IL-17F produced by ILC3s in host defense against C. albicans in the epidermis. The results also suggest that epidermal C. albicans clearance is independent of innate immune receptors or that these receptors act redundantly in fungal recognition and clearance. Abstract : A new model delineates immune responses in epidermal candidiasis Graphical Abstract: